Rethinking the unitary-federation classification: Towards a typology approach and performance analysis - Zuriana, Zahrin (2023)
In the 20th century, regionalization and decentralisation have brought a new paradigm for the division of power, enhancing subnational capability and power distribution across boundaries. These two global trends, which indirectly promoted "federalization processes" in unitary countries, made unitary and federated territorial management and power-sharing hard to discern. This drives the Unitary vs. Federation System dichotomy to become incongruous, and the existing classification is no longer relevant. In order to rethink the classification, this study aims to construct a typology of government systems. This first objective was accomplished during Phase I, which followed Kluge's qualitative model, “Empirically Grounded Type of Construction” which involves four steps. This study, however, employed a mixed method using nested concurrent strategies. Only the first step applied qualitative library research, the remaining step employed quantitative methods. The second step involves hybrid clustering analysis (hierarchical, two-step, and k-means analyses served as the primary analyses), the third step involves correlation test, and the fourth step involves ANOVA, Kruskal-Wallis, descriptive, and box plot analyses. This Phase I was successful in constructing a typology in which five clusters were found in n=70 countries and arranged in a continuum, starting from the left: Centralised Unitary, Decentralised Unitary, Regionalized Unitary, Centralised Federation, and Decentralised Federation at the right end. The second objective was to examine group that are likely to promote better performance in macroeconomics, fiscal and governance. This Phase II was done in quantitative inter-cluster analysis, and it was discovered that Regionalized Unitary was the best cluster, followed by Decentralised Federation, Centralised Federation, Decentralised Unitary, and Centralised Unitary. This study determined that the distribution of authority to subordinate units is crucial for optimal government functioning. This governmental system classification is a fundamental theoretical contribution of Unitary vs. Federation Systems that translates into a new understanding of governmental systems. This study also contributes to the clustering method that will be required for future comparable studies. Finally, this study provides fundamental reference or guidelines for countries that are pursuing the federalism prospect and looking for the best governance, economic, and fiscal arrangements.